Soft values based detector for bit interleaved coded modulation multi input multi output systems - Amjad N. Jabir; Atyaf Sami Noori (Institute of Advanced Engineering and Science, 2022)
With the advantages of spatial multiplexing multi input multi output (MIMO) systems in terms of high transmission capacity, the high complexity of the detector at the receiver side of such systems is a major issue. Performance, in terms of bit error rate (BER) is studied for bit interleaved coded modulation (BICM) MIMO systems. List based generation of (bits) soft values is considered for 2 by 2, 4 by 4 systems with 16,64 quadrature amplitude modulation (QAM) and different list sizes utilizing a non systematic convolutional code. Using a sphere detector partial tree search, a scheme is suggested and shown to be more computationally efficient (in terms of the average number of scanned nodes) than a reported alternative for block, flat fading channels. Simulation results reveal that performance in terms of BER can still be maintained.